More on Plastic Yield Criteria - Partom, Yehuda (European Journal of Applied Sciences, 2022)
The two plastic yield criteria known as MISES and TRESCA were proposed long ago. The Mises criterion is the one usually preferred by the strength of materials community, but tests have shown that Tresca’s criterion is the more accurate. We discuss here the two criteria, and based on those tests we conclude in favor of the Tresca criterion. But the two criteria are not that different, so when accuracy is not important, Mises may serve as a simple approximation to Tresca.